(3JMaI GdCfaS hTYGQ Cgd GdGfOdSs - (3Ydj Hf YHO GdQMef GdgRjds
(3ChdgG (B:s
(3GdMeO ddg GdefYe HShGHZ Gdeff hGdGdGA CeG HYO cJH Gddg GdfUQ GdeDjO hGdKfGA GdeNdO dCejQ GdeSdejf GdZfi HGddg CHj YHO Gddg eMeO GHf ehdGfG CejQ GdeSdejf s
(3BNQgG (B:s
(3bGd GHh GdWjH Cf GdSdGM LejY GdfGS jMedg hdjS cd PhGJ GdeNda GdSHY , hgfG HMeO Gddg GfJgjJ Edi eG bUOJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B243s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(5095) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs